Psychological effect of brand image and brand reputation on sustainable firm performance in Indonesian logistics - Danes Jaya Negara; Bambang Mantikei; Meitiana; Usup Riassy Christa; Lelo Sintani (Contemporary Economics, 2020)
The study examines the relationship between brand image, brand reputation, brand goodwill, and sustainable firm performance (FP). The purpose was to examine the psychological effect of brand image and brand reputation on sustainable FP of Indonesian logistics companies. This was achieved using primary data collected through questionnaires. 500 questionnaires were distributed, and 270 valid responses were used for data analysis, which used Smart PLS for that purpose logistics companies logistics companies. Results of the study highlighted that brand image and brand reputation has significant psychological effect on sustainable FP of logistics companies. Any change in the brand image and brand reputation has significant psychological effect which has contribution to decrease or increase the sustainable FP. Moreover, goodwill also has important role in sustainable FP. Both brand image and brand reputation effect on brand goodwill and finally, brand goodwill influences the sustainable FP.
Keywords: D91; L25; 330; Brand image; brand reputation; sustainable firm performance; brand goodwill; psychological effect